Validitas Pengembangan Media Pembelajaran Kartu Kuartet Berbasis Pictorial Riddle Materi Penerapan Sila-sila Pancasila Siswa Kelas III SDN Mrican 1 - Dwi Rahmawati Fatimah; Frans Aditia Wiguna; Karimatus Saidah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study was motivated by the limited use of instructional media for the Pancasila Education subject in Grade III at SDN Mrican 1, which resulted in low student engagement during the learning process. Furthermore, the topic regarding the application of Pancasila principles was considered difficult for students to grasp, creating a need for instructional media. The objective of this study was to determine the validity of